Self-expectations, socially prescribed expectations, and wellness in 14- to 15-year-old athletes, ballet, and music students in Norwegian talent schools - An interview study - Stornæs, A. V.; Sundgot-Borgen, J.; Pettersen, G.; Rosenvinge, J. H.; Nordin-Bates, S. M. (The Sport Psychologist, 2023)
Talent-school settings may generate stress via demanding expectations. To investigate students representing Norway`s growing phenomenon of early adolescent talent schools, we interviewed twenty-seven 14- to15-year-old boys and girls about their experiences with self- and socially imposed expectations. Students were recruited from two sports schools (n = 14) and one school each with talent classes for ballet (n = 7) and music (n = 6). Using reflexive thematic analysis, we found four main themes representing the performers` accounts of (a) self-oriented expectations of persistent hard work, evoking self-doubts, and never-give-up attitudes; (b) coaches`/teachers` socially prescribed expectations, stimulating hard work, and pursuit of approval and opportunities; (c) parental expectations, reflected as helpful support, concerns of letting parents down, and negotiating independence; and (d) struggles with balancing expectations, reflected by demanding workloads, difficulties with prioritizing recovery, and ill-being. Early interventions targeting unhealthy self- and socially imposed expectations in high-expectation settings may be required to safeguard youth performers` healthy development.